Water evaporation from cracked soil under moist conditions as related to crack properties and near‐surface wind speed. (5th January 2020) - Poulsen, Tjalfe G.; Cai, Weiling; Garg, Ankit
Abstract: The impacts of five factors (wind speed, crack width, crack distance, crack depth and crack orientation (compared to wind direction)), on evaporation from cracked soil under moist soil conditions were investigated experimentally. Experiments were carried out under laboratory conditions in a wind tunnel with a 1 m × 1 m × 2.5 m test section using large‐scale (50 cm diameter, 25 cm depth) samples of natural soils wetted to a soil water content of 0.2 g g −1 . To reduce the number of necessary experiments, a 2 k factorial experimental design was used. Crack widths, crack distances, crack depths and crack orientations of 5–20 mm, 40–100 mm, 50–200 mm and 0–90°, respectively, were used. Effects of each factor on evaporation rate, individually and by interaction between multiple factors, were subsequently calculated. Results showed that individual effects of all five factors on evaporation rate were significant at the 95% level. Wind speed had the largest impact on evaporation rate, followed by crack width, crack distance, crack depth and crack orientation in that order. Overall, the four crack properties together explained 47% of the variations in evaporation rate. Highlights: Evaporation from cracked, moist soil under windy conditions was investigated. Crack orientation significantly affects wind conditions close to the surface. Both wind speed and crack properties significantly affected evaporation rate. Crack properties together explained 47% of variations in evaporation rate.